Interactive form & space. - Chin, Joyce Huishan. (2010)
Human beings are changeable creatures. Throughout our lives, we change incessantly, inevitably, physically, mentally, consciously or unconsciously. Upon examining the architecture of today, essentially made up of static, solid objects, of single-function spaces filled with single-function elements, seem to be stagnating and restrictive, rather than reflecting life as it is today which calls for swift adaptability and versatility. It signifies a need for us to rethink and challenge architecture, interior design and furniture beyond its conventional static and single-function design, alluding to the possibility of a new kind of architecture as technologically, socially and economically we have transcended.